The determinants of acceptance towards takaful among working adults in small town of Perak - Ng, Aaron Jia Wei; Lee, Heng Xue; Ling, Leong Wei; Tan, Jit Tao (2024)
This research aims to examine and evaluate the acceptance of Takaful among the working adults in small towns of Perak with the mediator effect of Fintech. The study employs a primary data collection method using Google Form questionnaire and survey to the targeted respondents aged between 21 to 64 years old. There are a total of five variables used in the study, including three independent variables (Awareness, Service Quality, Human Resources), one dependent variable (Acceptance of Takaful), and one mediator variable (Fintech). A total 384 questionnaires were collected for the data analysis. The responses collected were analysed using the SmartPLS 4 analysis software. The research found that only 5 out of 7 hypothesis developments were significant, while the remaining 2 were insignificant. The results shows that Awareness and Human Resources have significant impacts on the Acceptance of Takaful for both direct and indirect relationships with the mediator “Fintech”. Otherwise, Service Quality do not significantly impact the Acceptance of Takaful for both direct and indirect relationships with the mediator “Fintech”. Moreover, the research provides useful data on the implications, limitations, and recommendations, and useful reference for future research relating to this topic.